An insight on the thermo-mechanical behaviour of deep core hybrid moulds - C. Gomes (2007)
Precision products are coming into the marketafter increasingly shorter periods of developmentand production. This implies reduced designperiods for the products and the tools. Themouldmaking industry is facing this reality byintegrating the stages of conception, developmentand tool manufacturing in the design process. Thisintegration use alternative fabrication technologiesemployed in rapid prototyping and tooling. Shorterlots of plastic components are consequentlybecoming possible through the use of hybridmoulds that use alternative non-metallic/metallicmaterials in the moulding blocks. Theconsideration of the wear and thermalcharacteristics of the moulding blocks areimportant for guaranteeing the precisionperformance of the hybrid moulds.The implementation of CAE tools during thedevelopment of an injection mould for a newproduct has already shown advantages. They canbe used to foresee the mould behaviour during theinjection moulding process without even startbuilding the tool and minimise the risk of mistakeduring the design process.Aspects associated to the design and performanceof an injection hybrid mould for a deep part areconsidered in this paper. Conventional Machining,Resin Casting and Prometal technologies wereused to produce the moulding cores. In particular,the mechanical and the thermal behaviour of thesehybrid components were assessed and comparedwith CAE simulations. The injection mouldingprogramme was carried out with unreinforcedpolypropylene.IntroductionThe mould making industry has been pressed